Two new species and a new country record of the genus Achalinus (Reptilia: Squamata: Xenodermidae) from China - Hou, Shao-Bing; Wang, Kai; Guo, Peng; Chen, Jin-Min; Yuan, Zhi-Yong; Che, Jing (Zootaxa, 2021)
Combining the results from morphological and molecular analyses, we explore the taxonomy of the genus Achalinus from Southwest China. As a result, we describe two new species, A. panzhihuaensis sp. nov. and A. yangdatongi sp. nov. from southern Sichuan and southern Yunnan provinces, respectively, and we record a new country record, A. emilyae, from Guangxi Zhuang A. R.. The mitochondrial genealogy suggests that A. panzhihuaensis sp. nov. is sister to A. meiguensis, while A. yangdatongi sp. nov. clusters with the sister species A. juliani and A. ater. Both new species show considerable genetic divergence from their recognized congeners (uncorrected p-distance > 6.2 % in COI gene). Furthermore, both new species can be diagnosed from closely related congeners by a combination of pholidosis characters. With our discovery, we provide a revised key to the 13 species from China and discuss some of the remaining issues regarding the taxonomy of the genus in China.